CORRELATION BETWEEN BRUXISM, OCCLUSAL DYSFUNCTION AND MUSCULO-ARTICULAR STATUS - Simona Maria Iacob; Andrea Maria Chisnoiu; Adriana Objelean; Mirela Ioana Fluerașu; Roxana Reghina Moga; Smaranda Dana Buduru (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study. The objective of the current study is to determine if a correlation exists between bruxism and occlusal dysfunction. It was also investigated whether bruxism is influenced by musclo-articular status and/or is associated with dental-periodontal pathologies including dental wear, dental fissures, gingival retraction or abnormal dental mobility. Materials and method. The study was carried out in two stages. In the first phase an original bruxism questionnaire was distributed to the 180 subjects included in the study. Based on the answers two groups were formed: subjects with self-reported bruxism (n=60) and the second group without bruxism (n=120). In the second phase an intraoral examination was performed, including static and dynamic occlusion, masticatory muscles and temporomandibular joint (TMJ) evaluation. Dental signs of bruxism were also identified and registered (dental wear, gingival retraction or dental mobility). Results. Occlusal dysfunction and TMJ pain (83,3% vs 16,7%) or disc displacement (80% vs. 20%) were more frequently diagnosed in patients with bruxism. A significant correlation (p<0,005) was observed between the presence of bruxism and muscle pain, hypertonia and/or hypertrophy (63%). Conclusion. Bruxism is more frequent in patients presenting occlusal imbalance. Dental signs in patients with bruxism are represented by pathological wear, dental fissures or fractures, mobility and gingival retraction. Jaw muscle symptoms (such as pain, hypertonia or hypertrophy) and temporomandibular joint signs (pain or/and disc displacement) often coexist with bruxism.